Photocatalytic mineralization of brilliant green dye using bimetallic CeCuO3 nanoparticles in LEDs irradiations: A green and economically viable approach - Keshav Lalit Ameta; Jyoti Sharma; Vijendra Singh Solanki (Results in Chemistry, 2022)
The use of bimetallic nanoparticles in photocatalysis is one of the prominent techniques for the treatment of wastewater. Pure and N, S-co-doped bimetallic cerium copper oxide nanoparticles were prepared and characterized by FTIR, X-ray diffraction and SEM. Newly synthesized N, S-co-doped CeCuO3 NP’s were used as photocatalysts for the degradation of Brilliant green dye in the presence of ecofriendly LEDs (250 W) irradiations. The values of rate constant for N, S co-doped and undoped CeCuO3 was observed individually. Brilliant green dye was effectively degraded by N, S doped CeCuO3 as compared to undoped CeCuO3 nanoparticles. Effect of doping and operating parameters e.g. pH, Intensity of light and amount of catalyst etc., on the rate of mineralization of dye was studied. Overall degradation of dye was confirmed by the determination of COD, CO2 and UV–Visible investigation of the samples. The mechanism of the mineralization of dye molecules was investigated by the formation of •OH radicals in the aqueous suspension. The reusability of catalyst was tested by different cycles.